Electron-phonon interactions in GaAs droplet quantum dots characterized by temperature-dependent optical transitions - Park, Sein; Kim, Yongmin; SONG, JIN DONG (한국물리학회, 2025)
We investigate the photoluminescence (PL) characteristics of GaAs quantum dots (QDs) fabricated via droplet epitaxy as a function of temperature. With increasing temperature, the PL peak energy and integrated PL intensity decrease, while the full width at half maximum (FWHM) broadens. These variations are attributed to enhanced phonon interactions and carrier dynamics. Specifically, the reduction in transition energy and the FWHM broadening are attributed to electron-phonon interactions, whereas the decline in integrated PL intensity is associated with carrier transfer and exciton dissociation.